The Effect of Reciprocal Learning Model Assisted by IT Media and Social Skills Towards Student Learning Outcomes - Sri Harmaida Rahayu; Ibnu Hajar; Hidayat Hidayat (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The aims of this study are: 1) differences in students learning outcomes of Social Sciences Subject taught with Reciprocal learning model assisted by IT media with students learning outcomes of Social Sciences Subject taught with Reciprocal learning model without IT media, 2) Differences in students learning outcomes of Social Sciences Subject who have personal social skills with students learning outcomes of Social Sciences Subject who have peer tutoring social skills, and 3) Interactions between Reciprocal learning model are assisted by IT media and Reciprocal learning model without using IT media with social skills on students learning outcomes of Social Sciences Subject. The research is conducted in Public Elementary School (SDN) 101794 Patumbak which is located in Pertahanan Street, Pasar VII, Patumbak I. The population in this study are 4th grade students in Public Elementary School (SDN) 101794 in the 2016/2017 Academic Year which amounted to 60 students. 4thA grade were 30 students and 4th B were 30 students. Data collection techniques uses in this study are observation techniques with social skills observation sheet instruments, besides that in this study also uses learning outcomes test instruments. Data analysis techniques in this study uses Two Way Anova. The results show that: (1) There are significant differences between students learning outcomes of Social Sciences Subject taught with Reciprocal learning model assisted by IT media with students learning outcomes of Social Sciences Subject taught with Reciprocal learning model without IT media (Fhitung = 17.064 and sig. 0.000> 0.05 ); (2) There is a significant difference between students learning outcomes of Social Sciences Subject who have personal social skills with students learning outcomes of Social Sciences Subject who have peer tutoring social skills (Fhitung= 10.602 and sig values. 0.000> 0.05); (3) There is an interaction between reciprocal learning model and social skills towards students’ learning outcomes of Social Science Subject (Fhitung = 22,115 and sig. 0,000> 0,05).